PERAN KELUARGA DALAM PERAWATAN KAKI DIABETES MELLITUS DI PUSKESMAS KARANGNONGKO KLATEN JAWA TENGAH - Elisa Ambarwati, Mei; Prabowo, Tri; Suwarno (Jurnal Media Ilmu Kesehatan, 2014)
Background: Diabetic ulcer is one of the chronic complications of diabetes mellitus. It often impact problems in the family during the treatment process. Family plays a functional role in implementing health care practices such as delivering foot care on  family members  who  suffer from  diabetes mellitus.  T h i s m e t h o d i s a preventative measure to prevent the occurrence of diabetic wounds. Family's ability to provide health care can affect the health status of those family members. Families who can carry out the task of health might resolve the health problems. Objective: To determine the family role in foot care to diabetic mellitus patients in Puskesmas Karangnongko Klaten Jawa Tengah. Methods: This was a qualitative research used phenomenology,  and  employed  in-depth interviews. Participants were obtained purposively, 5 families were involved. Results: There were families who do not understand their role in recognizing the problem in patients with diabetes mellitus. Families had lack understanding about their role in decision making regarding the importance of foot care and its role in modifying the environment to ensure the health of the patient. Families had understanding about their role in caring for family members who suffer from diabetes and its role in the use of health care facilities that exist around their areas. Conclusions: The family role in foot care to diabetic mellitus patients in Puskesmas Karangnongko Klaten Jawa Tengah needs to be improved, because there are many families who have lack understanding on  foot care in diabetic patients. Keywords : Family Role, Foot Care, Diabetic Mellitus.